The integrated practitioner - Amery, Justin (Intergrated practitioner series, 2014)
It explores the relationship between practitioners and their tangible, external tools such as time, computers, money, information, colleagues, equipment, targets and office spaces, along with less tangible elements like knowledge, understanding, language, values and beliefs. These tools can be of great benefit when fully integrated and balanced but they often end up controlling practitioners, dictating the manner in which the practice operates and ultimately reducing efficacy. It suggests ways for practitioners to harness the positive forces of these tools and regain control